Through the Spherical Looking‐Glass: Asymmetry Enables Multicolored Internal Reflection in Cholesteric Liquid Crystal Shells. Issue 1 (20th November 2017) - Geng, Yong; Jang, Ju‐Hyun; Noh, Kyung‐Gyu; Noh, JungHyun; Lagerwall, Jan P. F.; Park, Soo‐Young
Abstract: Spheres of cholesteric liquid crystal generate dynamic patterns due to selective reflection from a helical structure subject to continuously curved boundaries. So far the patterns are investigated exclusively as function of reflections at the sphere exterior. Here it is shown that the cholesteric shells in a microfluidics produced double emulsion enable also a sequence of internal reflections if the shells have sufficiently thin top and thick bottom. While such asymmetry is promoted by buoyancy when the internal droplet has lower density than the liquid crystal, the elasticity of the cholesteric helix prefers a symmetric shell geometry, acting against gravity. This subtle balance can hide the internal reflections for long time. Eventually, however, the asymmetry is established, revealing a new class of photonic patterns characterized by colored sharp concentric rings. With the complete knowledge of the diverse light‐reflecting behavior of cholesteric liquid crystal shells, and utilizing the tunability of the structure period by, e.g., temperature, electric field, or exposure to various chemical species as well as polymer stabilization for making the shells long‐term stable, they may be developed into remarkable new optical elements for photonics, sensing, or security pattern generation. Abstract : Shells of cholesteric liquid crystal can exhibit colorful rings from internal selective reflection. The shell must be thinner at the top than at the bottom, as promoted by buoyancy if the internal liquid has lower density than the liquid crystal. However, such asymmetry is counteracted by the elasticity of the helix, which favors uniform shell thickness.